2016
DOI: 10.1097/01.aoa.0000482632.65442.c8
|View full text |Cite
|
Sign up to set email alerts
|

Society for Maternal-Fetal Medicine (SMFM) Clinical Guideline #8: The Fetus at Risk for Anemia—Diagnosis and Management

Abstract: (Am J Obstet Gynecol. 2015;212(6):697–710) Fetal anemia is a life-threatening condition that is typically caused by red cell alloimmunization or parvovirus infection, but can also result from a variety of other causes. The purpose of this review was to enumerate the various causes of fetal anemia and outline surveillance options and management strategies. The authors performed a systematic search for relevant articles in the following online databases: MEDLINE, PubMed, EMBASE, and the Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 0 publications
1
53
0
5
Order By: Relevance
“…For the cases without the results of fetal serological tests, the diagnosis was made by the parental phenotypes of the MN blood group and the clinical manifestations of the anemia fetus. Cordocentesis was performed when the peak systolic velocity of the middle cerebral artery (MCA‐PSV) was >1.50 multiples of the median 20 . The intrauterine transfusion (IUT) indication was followed by the fetal anemia guidelines 20 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the cases without the results of fetal serological tests, the diagnosis was made by the parental phenotypes of the MN blood group and the clinical manifestations of the anemia fetus. Cordocentesis was performed when the peak systolic velocity of the middle cerebral artery (MCA‐PSV) was >1.50 multiples of the median 20 . The intrauterine transfusion (IUT) indication was followed by the fetal anemia guidelines 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Cordocentesis was performed when the peak systolic velocity of the middle cerebral artery (MCA‐PSV) was >1.50 multiples of the median 20 . The intrauterine transfusion (IUT) indication was followed by the fetal anemia guidelines 20 . During the study period, 19 women had a pregnancy with anti‐M, but only 11 had HDFN cases related to anti‐M.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this survey, it was noteworthy that 5 of 16 cases (31%) of red‐cell alloimmunization were caused by the anti‐Jra antibody. The anti‐Jra antibody has generally been believed to be a relatively uncommon cause of hemolytic disease in fetuses and newborns (HDFN) for decades 12, 13 . However, some investigators recently reported several cases of HDFN induced by anti‐Jra antibody 14, 15, 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Once the fetuses develop pre‐hydropic signs, especially cardiomegaly or increased MCA‐PSV, fetal anaemia should be assessed and IUT should be offered when the haematocrit is <30%, as practiced in other causes of fetal anaemia, e.g. rhesus isoimmunisation 11 . However, the blood of these fetuses consists of a significant proportion of Hb Barts, which has a limitation in oxygen transfer.…”
Section: Mother Father Fetus (Before Treatment) Newborn At Birth At Follow‐up Visitsmentioning
confidence: 99%